2019
DOI: 10.1007/s13197-019-04064-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood fruit (Haematocarpus validus (Miers.) Bakh. f. ex Forman): a novel source of natural food colourant

Abstract: Plant based pigments have widely been used by human beings since ancient times. These pigments, being natural in origin, have better acceptability amongst the consumers and offer diversified applications worldwide. For identification of novel pigment sources, lesser known species need to be studied systematically. In the present report, a tropical fruit species viz. blood fruit was studied for its physicochemical parameters and anthocyanin content. Fruit pulp had total soluble solids of 17 °B with acidic pH (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…The results of anthocyanins obtained for both the samples are comparable with the anthocyanins content of the same fruit of Andaman Island studied by Bohra et al. (2020).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of anthocyanins obtained for both the samples are comparable with the anthocyanins content of the same fruit of Andaman Island studied by Bohra et al. (2020).…”
Section: Resultssupporting
confidence: 88%
“…The results of individual anthocyanins obtained in the current study indicated that cyanidin-3-glucoside (cy3g) which is known, as a potential antioxidant was highly concentrated in UAE-M (2.303 mg/g) compared with CE-M (2.056 mg/g). The results of anthocyanins obtained for both the samples are comparable with the anthocyanins content of the same fruit of Andaman Island studied byBohra et al (2020).…”
supporting
confidence: 80%
“…The species has been identified as a novel source of natural colourant, Pelargonidin and Cyanidin being the dominant compounds responsible for its colour. 1 Considering potential of this species as a fresh fruit, natural colourant, source of bioactive compounds and as a viable source of income for local people, it being promoted as a novel crop in the Andaman and Nicobar Islands. [1][2][3] However, forests are the major source of blood fruit for local people in native regions and its natural populations have been threatened due to manmade and natural calamities.…”
Section: Introductionmentioning
confidence: 99%
“…1 Considering potential of this species as a fresh fruit, natural colourant, source of bioactive compounds and as a viable source of income for local people, it being promoted as a novel crop in the Andaman and Nicobar Islands. [1][2][3] However, forests are the major source of blood fruit for local people in native regions and its natural populations have been threatened due to manmade and natural calamities. In order to conserve the species, seed pretreatment for improving seed germination was standardized.…”
Section: Introductionmentioning
confidence: 99%
“…For potential species having limited distribution as in case of Haematocarpus validus, seed germination could help in generating diversity which could be tapped in the years to come. 3 Some underutilized species are wild relatives of cultivated crops, which could be screened for their potential as source of gene/ rootstock for cultivated types. Garcinia cowa, a common species in the Northeastern region and the Bay islands, is a potential species as backyard crop as well as rootstock for Mangosteen (Garcinia mangostana).…”
mentioning
confidence: 99%